Perancangan Iklan TVC Perumahan Cerme Square Residence dengan Teknik Animasi 3D Sebagai Upaya Meningkatkan Brand Awareness - Prayoga, Al Lukman Arif; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
The purpose of the design of the housing TVC advertising Cerme Square Residence is to raise awareness and facilitate the community to do its needs. This research was conducted with qualitative research methods that will conduct interviews, observation, documentation, and literacy to formulate the concept of advertising TVC. Analysis of data using multiple stages, namely data reduction, data presentation, and conclusion. After the data is analyzed, it was found the design concept or keyword of TVC advertising design of